Use of perennial plants in the fight against gastrointestinal nematodes of sheep - Bosco, Antonio; Prigioniero, Antonello; Falzarano, Alessandra; Maurelli, Maria Paola; Rinaldi, Laura; Cringoli, Giuseppe; Quaranta, Giovanni; Claps, Salvatore; Sciarrillo, Rosaria; Guarino, Carmine; Scarano, Pierpaolo (Frontiers in Parasitology, 2023)
Background Gastrointestinal nematodes (GINs) are a serious problem in ruminant pastures worldwide. They generate production losses, from the point of view of both the food chain and animal mortality. This study provides preliminary results concerning the use of pasture plants in the Campania region (of southern Italy) to control GINs in sheep. Methods Sixteen species of wild and cultivated perennial plants present in seminatural pastures were sampled. All species were extracted with the conventional maceration technique, using three different solvents (i.e., H2O, EtOH, and an EtOH:H2O (8:2) mixture) in order to extract different bioactive compounds. The total phenolic content (TPC; assessed via the Folin–Ciocȃlteu assay) of all extract samples was preliminarily characterized. Each sample was aliquoted across six different concentrations and an in vitro egg hatching test (EHT) was conducted to evaluate the ovicidal effect on sheep GINs. Results The results indicated that Cichorium intybus L. and Foeniculum vulgare Mill. extracts greatly inhibited egg hatching within 48 hours of exposure, showing efficacy (≥ 62.6%) at the three higher concentrations when compared with the other plants. Conclusion The use of extracts of wild and cultivated perennial plant species in pastures can be a valid alternative to the use of synthetic anthelmintic drugs, which can generate problems, such as anthelmintic resistance, in the long term. Looking forward, further in vitro studies that evaluate the in vitro effect of these extracts on ruminant cell cultures, and field application through in vivo studies, would likely confirm the results obtained from preliminary in vitro EHTs. All these studies should be aimed at evaluating the therapeutic potential and future applicability of specific plant cultures in pastures to achieve sustainable pest control.